Dynamic agricultural systems : economic prediction and control - Rausser, Gordon C.; Hochman, Eithan; Wilkinson, Maurice (New York : North Holland, 1979)
This book emphasize the conceptual and technical aspects of control theory in the context of dynamic economic systems.
Includes index.
Includes bibliographical references: p. 343-353.
ucj 17/01/2019
Loans
Keywords: Agriculture; Operations research; Control theory